2004
DOI: 10.1074/jbc.m401235200
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating Hormone Activation of Hypoxia-inducible Factor-1 by the Phosphatidylinositol 3-Kinase/AKT/Ras Homolog Enriched in Brain (Rheb)/Mammalian Target of Rapamycin (mTOR) Pathway Is Necessary for Induction of Select Protein Markers of Follicular Differentiation

Abstract: We sought to elucidate the role of AKT in folliclestimulating hormone (FSH)-mediated granulosa cell (GC) differentiation. Our results define a signaling pathway in GCs whereby the inactivating phosphorylation of tuberin downstream of phosphatidylinositol (PI) 3-kinase/AKT activity leads to Rheb (Ras homolog enriched in brain) and subsequent mTOR (mammalian target of rapamycin) activation. mTOR then stimulates translation by phosphorylating p70 S6 kinase and, consequently, the 40 S ribosomal protein S6. Activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
191
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(211 citation statements)
references
References 86 publications
18
191
0
2
Order By: Relevance
“…However, little was known about the mechanism of FSH stimulation on VEGF expression. Other studies showed HIF-1α and survivin may play a role in VEGF expression [7][8][9][10][13][14][15][16], and it had also been shown that FSH induces HIF-1α and survivin expression [37][38][39]. In this study, we showed that treatment with FSH also increased survivin and HIF-1α expression (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, little was known about the mechanism of FSH stimulation on VEGF expression. Other studies showed HIF-1α and survivin may play a role in VEGF expression [7][8][9][10][13][14][15][16], and it had also been shown that FSH induces HIF-1α and survivin expression [37][38][39]. In this study, we showed that treatment with FSH also increased survivin and HIF-1α expression (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 66%
“…FSH stimulated PI3K/AKT signal transduction in many cells, including granular cells, Sertoli cells, and oocytes [39][40][41]. FSH has also been shown to activate ERK and p38 mitogen-activated protein kinase (MAPK) in granulose cells [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…74 The sequelae of this interaction are not yet known, but may be part of the mechanism by which FSH activates the Akt/PKB pathway. 75 Indeed, in rat granulosa cells, adiponectin provokes phosphorylation of Akt/PKB, 40 and in other tissues Evidence indicates that FSH can also interact with APPL1, presumably via the C-terminal intracellular domain, with the potential, and it is further known that FSH via unknown intermediates, induces phosphoinosital-3 kinase activation and thus the Akt or protein kinase B pathway. Insulin likewise functions through this mechanism, although direct interaction between the insulin receptor and APPL1 has not been shown.…”
Section: Mechanisms Of Action Of Adiponectin In Reproductive Tissuesmentioning
confidence: 99%
“…In addition to this hypoxia-dependent mechanism, recent studies have demonstrated non-hypoxic pathways for regulation of HIF-1␣ activity (9,10) and multiple regulatory mechanisms of HIF-1␣ protein level, may enable cells to adapt to diverse alteration of environments and preserve homeostasis in a tissue-dependent manner. For example, receptor-mediated regulation of HIF-1␣ expression is thought to be cell and signal specific, and a number of reports have suggested that receptor-mediated factors such as growth factors, hormones, and cytokines induce HIF-1␣ protein expression through various signalings including PI3K/mammalian target of rapamycin (mTOR) pathway (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%